Identification of a complex genomic rearrangement in TMPRSS3 by massively parallel sequencing in Chinese cases with prelingual hearing loss. Issue 6 (23rd April 2019) - Li, Xinlei; Tan, Bo; Wang, Xiaoqian; Xu, Xiaofei; Wang, Cuicui; Zhong, Mingjun; Zhao, Qiuling; Bao, Zhongwei; Peng, Weihua; Zhang, Lei; Cheng, Jing; Lu, Yu; et al.
Abstract: Background: Genetic variants in TMPRSS3 have been causally linked to autosomal recessive nonsyndromic hearing loss (HL) at the DFNB8 and DFNB10 loci. These variants include both single nucleotide and copy number variations (CNVs). In this study, we aim to identify the genetic cause in three Chinese subjects with prelingual profound sensorineural HL. Methods: We applied targeted genomic enrichment and massively parallel sequencing to screen 110 genes associated with nonsyndromic HL in the three affected subjects. CNVplex ® analysis and polymerase chain reaction (PCR) were performed for CNV detection. Results: We identified biallelic variations in TMPRSS3 including a novel complex genomic rearrangement and a novel missense mutation, c.551T>C. We have mapped the breakpoints of the genomic rearrangement and showed that it consisted of two deletions and an inversion encompassing exon 3 to exon 9 of TMPRSS3 . Conclusion: Our study expanded the mutational spectrum of TMPRSS3 to include complex genomic rearrangements. It showcased the importance of an integrative approach to investigate CNVs and their contribution to HL. Abstract : In this paper, we reported a complex genomic rearrangement and a missense mutation in TMPRSS3 identified in Chinese cases with prelingual profound hearing loss (HL). Our study expanded the mutational spectrum of TMPRSS3 to include complex genomic rearrangements. It showcased the importance of an integrative approach to investigate copy number variations and their contribution to HL.